Life expectancy ranking of Canadians among the populations in selected OECD countries and its disparities among British Columbians - Zhang, Li Rita (Arch Public Health, 2015)
BACKGROUND: Canada is among the world’s leading nations with the longest life expectancy at birth (LE(0)), and British Columbia (BC) ranks top among Canadian provinces and territories for LE(0) in both men and women. This paper examined recent data as well as projected trends in LE(0) of Canadian men and women and explored the geographic and socioeconomic disparities in LE(0) specific to BC. METHODS: Using retrospective data on LE(0) and age-standardized mortality rates, Canada was compared to 11 other Organization for Economic Cooperation and Development (OECD) countries with the longest LE(0). Projections were made using linear regression modelling to the year of 2023. The association between regional LE(0) and regional socioeconomic status (SES) was examined for the province of BC using its Local Health Area (LHA) level data on SES and LE(0). RESULTS: In 2009, Canadian men (LE(0): 78.7 years) and women (LE(0): 83.3 years) ranked 7(th) and 8(th), respectively among the 12 OECD nations under comparison. Significantly smaller annual gains in LE(0) contributed to the losing of their top ranks in LE(0) for Canadian men and women in recent years, which was projected to sustain. Higher mortality risks, particularly for lung cancer and external causes of mortality among women was found for Canada compared to leading countries on these measures. Geographic variations were evident in LE(0) in BC, and there was a significant gap of 3.6 years in the average LE(0) for BC’s LHAs in the lowest SES tertile (78.6 years, 95% CI: 78.0-79.3) compared to those in the highest SES tertile (82.2 years, 95% CI: 81.6-82.8). CONCLUSIONS: Canada continues to remain one of the OECD countries with longest living population. With the highest LE(0) in the country, British Columbia has an opportunity to address socio-economic disparities in LE(0).